2008
DOI: 10.1002/adma.200701940
|View full text |Cite
|
Sign up to set email alerts
|

FeTiTaO6: A Lead‐Free Relaxor Ferroelectric Based on the Rutile Structure

Abstract: Several materials properties of rutile TiO 2 (together with its other polymorphs) have been widely investigated in view of both fundamental and practical interest. It is a wide band gap (E g ¼ 3.05 eV) semiconductor that finds application, among others, as a photocatalyst for splitting water [1] into H 2 and O 2 and remediation of organic pollutants. [2] Among the lesswell-known properties of TiO 2 is its abnormally large static dielectric permittivity that shows strong frequency dependence as well as the asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 41 publications
3
31
1
Order By: Relevance
“…A different C p (ω) behaviour of FTT01, sintered in CO 2 , is visible from Fig. 7(e), where C p (ω) also increases with temperature, but superposed humps are detectable at 500-600 K; the latter are reminiscent of maxima in C p (ω) vs. temperature data of relaxor ferroelectric-like rutile-type FeTiMO 6 (M= Ta,Nb) ceramics in the temperature range of 500-600 K [43,44,47,48], that were obviously to some part SE effects. For FNT005, sintered in air, Fig.…”
Section: Electrical Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…A different C p (ω) behaviour of FTT01, sintered in CO 2 , is visible from Fig. 7(e), where C p (ω) also increases with temperature, but superposed humps are detectable at 500-600 K; the latter are reminiscent of maxima in C p (ω) vs. temperature data of relaxor ferroelectric-like rutile-type FeTiMO 6 (M= Ta,Nb) ceramics in the temperature range of 500-600 K [43,44,47,48], that were obviously to some part SE effects. For FNT005, sintered in air, Fig.…”
Section: Electrical Propertiesmentioning
confidence: 95%
“…7(c) displays for FNT005 (air) a presentation of tan δ vs. frequency for various temperatures, whence for each temperature a low-and high-frequency peak is visible, arising from GB/SE and bulk relaxation processes, respectively. From these peaks, activation energies can be derived according to the relation f tanmax ∝ exp(−E Atan /k B T), with f tanmax the frequency at the maximum, E Atan the activation energy for a relaxation process to occur [41][42][43][44][45][46]. From data for several temperatures, E Atan =0.48 eV and 0.68 eV were deduced for bulk and GB/SE processes, respectively.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…The rutile represents a generic inorganic structure adopted by several metal oxides of the MO 2 , MM 0 O 4 and the MM 0 2 O 6 stoichiometries [6]. Some of the authors have recently reported [5,7] strong relaxor ferroelectric behavior for the rutile based oxide, FeTiTaO 6 , which is comparable to the best relaxor materials, such as the Pb 3 MgNb 2 O 9 and the Pb 3 ZnNb 2 O 9 . The significant development of the lead-free relaxors [8,9], extended their investigation into the dielectric properties to several other MM 0 O 4 and MTiM 0 O 6 , for the M = Fe, Cr, Ga and the M 0 = Nb, Ta, Sb rutile-type oxides for a better understanding of the origin in the ferroelectric response of the rutile based oxides in general.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Consequently, a great deal of effort has recently been put into exploring new RFE materials with higher T m value. [5][6][7][8][9][10][11][12] RFE exist in the different crystal structures that host ferroelectricity, including perovskites, tungsten bronzes, rutile structure, and Aurivillius phase. 7,8 In perovskites, RFE behavior occurs predominantly in lead-based complex compositions with the general formula Pb͑B 1 B 2 ͒O 3 , ͑B 1 =Mg 2+ ,Zn 2+ ,Ni 2+ ,Sc 3+ ..., B 2 =Nb 5+ ,Ta 5+ ,W 6+ ...͒ or lanthanum-substituted PbZr 1−x Ti x O 3 ͑PLZT͒.…”
Section: Introductionmentioning
confidence: 99%
“…21 Rutile-based FeTiTaO 6 is reported to be RFE with T m = 550 K at 530 Hz. 8 Aurivillius phase materials have generated increasing attention due to their potential use in nonvolatile ferroelectric random-access memory 22 and high-temperature piezoelectric applications. 23,24 Moreover, they are environment friendly lead-free piezoelectric materials.…”
Section: Introductionmentioning
confidence: 99%